Induced Pluripotent Stem Cells Enable Disease Modeling and Drug Screening in Calreticulin del52 and ins5 Myeloproliferative Neoplasms. Issue 7 (12th July 2021) - Secardin, Lise; Gomez Limia, Cintia; da Silva-Benedito, Suzana; Lordier, Larissa; El-Khoury, Mira; Marty, Caroline; Ianotto, Jean-Christophe; Raslova, Hana; Constantinescu, Stefan N.; Bonamino, Martín Hernán; Vainchenker, William; Monte-Mor, Barbara; et al.
Abstract : Mutations in the calreticulin ( CALR ) gene are seen in about 30% of essential thrombocythemia and primary myelofibrosis patients. To address the contribution of the human CALR mutants to the pathogenesis of myeloproliferative neoplasms (MPNs) in an endogenous context, we modeled the CALRdel52 and CALRins5 mutants by induced pluripotent stem cell (iPSC) technology using CD34 + progenitors from 4 patients. We describe here the generation of several clones of iPSC carrying heterozygous CALRdel52 or CALRins5 mutations. We showed that CALRdel52 induces a stronger increase in progenitors than CALRins5 and that both CALRdel52 and CALRins5 mutants favor an expansion of the megakaryocytic lineage. Moreover, we found that both CALRdel52 and CALRins5 mutants rendered colony forming unit–megakaryocyte (CFU-MK) independent from thrombopoietin (TPO), and promoted a mild constitutive activation level of signal transducer and activator of transcription 3 in megakaryocytes. Unexpectedly, a mild increase in the sensitivity of colony forming unit-granulocyte (CFU-G) to granulocyte-colony stimulating factor was also observed in iPSC CALRdel52 and CALRins5 compared with control iPSC. Moreover, CALRdel52-induced megakaryocytic spontaneous growth is more dependent on Janus kinase 2/phosphoinositide 3-kinase/extracellular signal-regulated kinase than TPO-mediated growth and opens a therapeutic window for treatments in CALR -mutated MPN. The iPSC models described here represent an interesting platform for testing newly developed inhibitors. Altogether, this study shows that CALR-mutated iPSC recapitulate MPN phenotypes in vitro and may be used for drug screening.